Exploring the Relationship Between Changes in Weight and Utterances in an Online Weight Loss Forum: A Content and Correlational Analysis Study - Hekler, Eric B; Dubey, Gaurav; McDonald, David W; Poole, Erika S; Li, Victor; Eikey, Elizabeth (JMIR Publications, 2014)
BackgroundThere is increasing interest in the use of online forums as a component of eHealth weight loss interventions. Although the research is mixed on the utility of online forums in general, results suggest that there is promise to this, particularly if the systems can be designed well to support healthful interactions that foster weight loss and continued engagement. ObjectiveThe purpose of this study was to examine the relationship between the styles of utterances individuals make on an online weight loss forum and week-to-week fluctuations in weight. This analysis was conducted to generate hypotheses on possible strategies that could be used to improve the overall design of online support groups to facilitate more healthful interactions. MethodsA convenience sample of individuals using an online weight loss forum (N=4132) included data both on online forum use and weight check-in data. All interactions were coded utilizing the Linguistic Inquiry and Word Count (LIWC) system. Mixed model analyses were conducted to examine the relationship between these LIWC variables and weight over time. ResultsResults suggested that increased use of past-tense verbs (P=.05) and motion (P=.02) were associated with lower weekly weights whereas increased use of conjunctions (eg, and, but, whereas; P=.001) and exclusion words (eg, but, without, exclude; P=.07) were both associated with higher weight during the weeks when these utterances were used more. ConclusionsThese results provide some insights on the styles of interactions that appear to be associated with weight fluctuations. Future work should explore the stability of these findings and also explore possibilities for fostering these types of interactions more explicitly within online weight loss forums.